Molecular mechanistic vision on binding interaction of triptan drug, a serotonin (5-HT1) agonist with human serum albumin through multispectral and computational assessments - Makegowda, Manjushree; Doddarevanna, Revanasiddappa Hosakere (European Journal of Chemistry, 2020)
The triptan drug such as eletriptan in combination with hydrochloride (ETP) is a 5-HT1 receptor agonist used to treat the migraine headache. Human serum albumin (HSA), the fundamental serum protein, executes various functions, that includes transporting and binding of many ligands. HSA binding interaction with ETP is elucidated from molecular docking in composite with fluorescence (emission, 3D and synchronous), UV-vis and FT-IR spectroscopy at 296, 304 and 312 K (pH = 7.40). ETP after interaction modified the HSA secondary structure and its micro-environments. Energy transfer and thermodynamic parameters were evaluated. Various quenching and binding constants were computed for formed ETP-HSA complex. The dominant interactive forces for ETP and HSA binding are hydrogen bonds join up with van der Waals extent possibly at site III (IB). The presence of Ca2+, Co2+, Na+, Mg2+ and Fe3+ ions significantly affected binding ability of ETP towards HSA. The essentialness of this investigation is beneficial in life sciences, medicinal chemistry, pharmaceutical industry and clinical medicine.